Proposal Hybrid CBC Encryption System to Protect E-mail Messages - Hashem, Soukaena Hassan (Iraqi Journal of Science, 2019)
Email is one of the most commonly utilized communication methods. The confidentiality, the integrity and the authenticity are always substantial in communication of the e-mail, mostly in the business utilize. However, these security goals can be ensured only when the cryptography is utilized. Cryptography is a procedure of changing unique data into a configuration with the end goal that it is just perused by the coveted beneficiary. It is utilized to shield data from other individuals for security purposes. Cryptography algorithms can be classified as symmetric and asymmetric methods. Symmetric methods can be classified as stream cipher and block cipher. There are different operation modes provided by the block cipher, these are Cipher Block Chaining (CBC), Output Feedback (OFB), Cipher Feedback (CFB) and Electronic Code Block (ECB). CBC used to complex the cryptographic systems, by using Initialization Vector (IV), Xoring, and encryption with specified key over chain of blocks, but CBC is vulnerable to chosen plaintext attack because the IV is static and vulnerable to chosen ciphertext attack because the encryption method with the key are static. This paper introduce a proposed E-mail messages encryption systems , the proposal based on modified CBC mode operation hybrid with some of techniques exploited in the encryption such as RADG, DNA, RNA and a suggested permutation methods. The proposed modifications applied on the CBC are generate IV randomly, generate key randomly, and propose encryption method, these modifications proposed to avoid the attacks that CBC is vulnerable to.